Benefits and Development Challenges for Conversion-Alloying Anode Materials in Na-Ion Batteries - Skurtveit, Amalie; Brennhagen, Anders; Park, Heesoo; Cavallo, Carmen; Koposov, Alexey Y. (Frontiers in Energy Research, 2022)
Over the past decade, Na-ion batteries (NIBs) have gained a substantial interest within the research community and relevant industry. NIBs are now emerging as a cost-effective and sustainable alternative to modern Li-ion batteries (LIBs). Similar to the parent LIB technology, NIB requires a new set of materials, which can boost battery capacity without sacrificing cycling stability, rate capabilities, and other performance targets. In NIB chemistry, anodes have received less attention compared to cathode chemistry, leaving hard carbon as a primary anode material, although its intercalation/adsorption mechanism limits the allowed number of Na-ions. Promising alternative groups of anodes are materials that undergo the combined conversion and alloying reactions (i.e., conversion-alloying anodes), due to the beneficial high theoretical capacity and good cycling stability. The conversion reaction in conversion-alloying anodes can be either reversible or irreversible, each possessing its advantages. However, the complexity of their operating mechanism(s) severely impedes their development. The present mini-review provides a survey of the recent developments of conversion-alloying-type anode materials for Na-ion batteries discussed in the context of their operation mechanism(s). Considering the chemical complexity of the conversion-alloying materials, the suggestions and guidance on characterization are provided along with theoretical considerations.